Pengaruh Penggunaan Model Group Investigation terhadap Kemampuan Literasi Sains Siswa Kelas IV SDN 017 Bonra Kecamatan Mapilli Kabupaten Polewali Mandar - Rahmawati Patta; Siti Raihan; Salman Usman (Departement of Mathematics Education, 2023)
This research is experimental research conducted to find out whether there is an effect of using the Group Investigation learning model on the scientific literacy abilities of class IV students at SDN 017 Bonra. This study aims to (1) find out the description of the use of the Group Investigation model in class IV of elementary school, (2) describe the ability of scientific literacy of class IV elementary school students, (3) find out the effect of the Group Investigation model on the ability of scientific literacy of class IV elementary school students. The research approach used is a quantitative approach with a quasi-experimental design research type. The population in this study were fourth grade students at SDN 017 Bonra with a sample of 32 students. The sampling technique used is probability sampling technique, namely simple random sampling technique. This study used two groups, namely the experimental group and the control group. Data collection techniques used in this study are observation, tests, and documentation. Data were collected from pretest and posttest administration and were then analyzed using descriptive statistics and inferential statistics using parametric statistical tests, namely the independent sample t-test. The results of the study showed that (1) the use of the Group Investigation learning model in the learning process was in a very good category, which was known from the proportion of model use in the class of 92.31%; (2) There is an increase in students' scientific literacy skills; (3) There is an effect of using the Group Investigation learning model on the scientific literacy skills of fourth grade students at SDN 017 Bonra, Mapilli District, Polewali Mandar Regency.